Characterisation of lymphocyte subpopulations in infantile haemangioma. Issue 10 (11th June 2015) - Tan, Elysia M S; Itinteang, Tinte; Chudakova, Daria A; Dunne, Jonathan C; Marsh, Reginald; Brasch, Helen D; Davis, Paul F; Tan, Swee T
Abstract : Aims: Interstitial CD45+ cells and T lymphocytes have previously been demonstrated within infantile haemangioma (IH). This study investigated the expression of B and T lymphocyte markers by the CD45+ population, and the expression of Thy-1, a marker of thymocyte progenitors, which have the ability to give rise to both B and T cells. Methods: Immunohistochemical (IHC) staining was performed on proliferating and involuted IHs for the expression of CD45, CD3, CD20, CD79a, Thy-1 and CD34. The presence of mRNA corresponding to CD45, CD3G, CD20 and Thy-1 was confirmed by reverse transcriptase-polymerase chain reaction in snap-frozen IH tissues. Cell counting of 3, 3-diaminobenzidine IHC-stained slides was performed on CD45+ only cells and dually stained CD45+/CD3+ cells or CD45+/CD20+ cells and analysed statistically. In situ hybridisation and mass spectrometry were also performed to confirm the presence and abundance of Thy-1, respectively. Results: IHC staining showed a subpopulation of CD45+ interstitial cells that expressed the T lymphocyte marker, CD3, and another subpopulation that expressed the B lymphocyte marker, CD20, in proliferating and diminished in involuted IHs. The abundant expression of Thy-1 on the endothelium of proliferating, but not involuted IH, was demonstrated by IHC staining and confirmed by in situ hybridisation and mass spectrometry. Conclusions: Both B and T lymphocytes are present within the interstitium of proliferating and involuted IH. The expression of Thy-1 by the endothelium suggests that B and T cells in IH may have originated from within the lesion, rather than migrating from the peripheral circulation.